Impact of a large and shallow twin-tunnel excavation on a high-speed railway bridge and related protective measures: A case study - Wenhui Yang; Dingwen Zhang; Daniela Boldini (Underground Space)
This case study examines a landmark engineering project in Suzhou, China, involving the construction of two large-diameter (13.2 m) shield tunnels beneath an active high-speed railway (HSR) bridge. This pioneering project is the first of its kind in both China and the world. Advanced numerical simulations were conducted to rigorously assess construction risks. To ensure the operational safety of the existing HSR bridge, an innovative protective system, consisting primarily of segmental steel casing concrete pile barriers, was employed. A comprehensive network of monitoring sensors was strategically deployed to track soil, pile barrier, and pier displacements throughout both the protective and tunnelling phases. Simulation results indicated that tunnelling without protective measures could cause pier displacements of up to 3.1 mm along the bridge—exceeding the maximum allowable displacement of 2 mm in accordance with regulations. Monitoring data revealed that the maximum pier displacement during protective scheme installation was limited to 0.5 mm. With these protective measures, pier displacement during each tunnelling phase remained consistently below 0.5 mm, representing an approximate 80% reduction compared to the unprotected scenario, thereby ensuring the continued safety of the HSR bridge.